2011
DOI: 10.2147/rred.s16282
|View full text |Cite
|
Sign up to set email alerts
|

Predicting response to incretin-based therapy

Abstract: There are two important incretin hormones, glucose-dependent insulin tropic polypeptide (GIP) and glucagon-like peptide-1 (GLP-1). The biological activities of GLP-1 include stimulation of glucose-dependent insulin secretion and insulin biosynthesis, inhibition of glucagon secretion and gastric emptying, and inhibition of food intake. GLP-1 appears to have a number of additional effects in the gastrointestinal tract and central nervous system. Incretin based therapy includes GLP-1 receptor agonists like human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…The group of patients in therapy with GLP-1 RA was not below the target threshold for HbA1c, in contrast to other studies such as that of Pratley et al [25], in which exenatide and liraglutide improved more the glycemic control if compared to DPP-4is. In accord with Sanjay et al [26], it has revealed that the only group that achieved the therapeutic target was treated with DPP-4i but these patients presented also a significantly lower starting HbA1c than those of the other two groups. Contrarily patients treated with GLP-1 RA had the highest HbA1c mean value before treatment but they did have the best HbA1c reduction, probably because patients with a higher initial HbA1c seem to have a greater glycemic response to therapy [26][27][28].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The group of patients in therapy with GLP-1 RA was not below the target threshold for HbA1c, in contrast to other studies such as that of Pratley et al [25], in which exenatide and liraglutide improved more the glycemic control if compared to DPP-4is. In accord with Sanjay et al [26], it has revealed that the only group that achieved the therapeutic target was treated with DPP-4i but these patients presented also a significantly lower starting HbA1c than those of the other two groups. Contrarily patients treated with GLP-1 RA had the highest HbA1c mean value before treatment but they did have the best HbA1c reduction, probably because patients with a higher initial HbA1c seem to have a greater glycemic response to therapy [26][27][28].…”
Section: Discussionsupporting
confidence: 76%
“…In accord with Sanjay et al [26], it has revealed that the only group that achieved the therapeutic target was treated with DPP-4i but these patients presented also a significantly lower starting HbA1c than those of the other two groups. Contrarily patients treated with GLP-1 RA had the highest HbA1c mean value before treatment but they did have the best HbA1c reduction, probably because patients with a higher initial HbA1c seem to have a greater glycemic response to therapy [26][27][28]. Incretin-based therapy in general and GLP-1 RA in particular, are often used for obese patients, because their mechanism of action delays gastric emptying, suppresses appetite, and improves satiety.…”
Section: Discussionsupporting
confidence: 76%
“…Within this group of patients, those with low glucagon values may respond better to SGLT2 inhibitors. Incretin-based therapy has been shown to be more effective in persons with high glucagon levels [ 32 ]. As these modes of treatment cause hyperinsulinemia, incretin-based therapy may prove more suitable for persons with a normal IGR.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%
“…This is especially true for trials involving incretin-based therapies, as their mechanism of action and response is closely linked with the autonomic nervous system. [ 16 ] This conjecture, however, is open to debate.…”
Section: S Ummarymentioning
confidence: 99%